Dentinal hypersensitivity?-Can this agent be the solution? - Pretha Madhu; Setty Swati; Ravindra S (Wolters Kluwer Medknow Publications, 2006)
AIM : To test the efficacy of desensitizing tooth paste containing EMS salts in alleviating dentinal hypersensitivity, reducing plaque accumulation, and reducing gingivitis. METHODS : A randomised, single blind, parallel placebo controlled study was conducted in 40 cases. The cases were randomly assigned to test and control groups. The test group was instructed to use the test tooth paste (containing EMS salts) and control group a placebo tooth paste (without any therapeutic agents) for a period of 6 weeks. The hypersensitivity levels were measured with scratchometer and verbal rating scale. Student t test and wilcoxon′s Mann-Whitney test were used to compare the test and control groups. RESULTS AND CONCLUSION : The results indicated that both the test as well as the control toothpastes were effective in alleviating dentinal hypersensitivity as well as reducing gingivitis. However, the test toothpaste was superior in alleviation of dentinal hypersensitivity.